Lispocephala Pokorny 1893 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Lispocephala Pokorny, 1893 Lispocephala Pokorny, 1893: 532. Type-species: Anthomyia alma Meigen, 1826, by original designation. Lispocephala alma (Meigen, 1826) Anthomyia alma Meigen, 1826: 188. Type-locality: not stated (probably Austria, Vienna). Holotype ♀, not located and presumed destroyed (Pont, 1986b: 211). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92). General distribution: Holarctic Region; in the Palaearctic, from Europe east to China. Lispocephala erythrocera (Robineau-Desvoidy, 1830) Caricea erythrocera Robineau-Desvoidy, 1830: 534. Type-localities: France, Saint-Sauveur and Paris. Syntypes, formerly in Robineau-Desvoidy collection, now destroyed (not MNHN). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92); Yamalo-Nenetskiy AO: Salekhard [as “Tobol’ skaya Guberniya, Obdorsk" in German], and Respublika Sakha: Amginskiy Ulus [as “Yakutsk (Amgin)” in German] (Hennig, 1961a: 485); Kurganskaya and Novosibirskaya Oblast’ (Sorokina, 2006a: 230); West and East Siberia (Pont, 1986a: 194). General distribution: Holarctic Region; in the Palaearctic, from Europe east to Japan. Lispocephala pallipalpis (Zetterstedt, 1845) Anthomyza pallipalpis Zetterstedt, 1845: 1678. Type-locality: Sweden, Lule Lappmark, Luleå. Lectotype ♂, MZLU (designated by Collin, 1963: 283; Pont, in press). Siberian records: Kurganskaya Oblast’ (Sorokina, 2006a: 230). General distribution: Holarctic Region; in the Palaearctic, from Europe, Russia (West Siberia), Japan; USA (New Hampshire). : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on pages 70-71, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Pokorny, E. (1893) Bemerkungen und Zusatze zu Prof. G. Strobl's \" Die Anthomyinen Steiermarks \". Verhandlungen der kaiserlich-koniglichen zoologisch-botanischen Gesellschaft in Wien, 43, 526 - 544.", "Meigen, J. W. (1826) Systematische Beschreibung der bekannten europaischen zweiflugeligen Insekten. Funfter Theil. Schultz, Hamm, xii + 412 pp.", "Pont, A. C. (1986 b) A revision of the Fanniidae and Muscidae described by J. W. Meigen (Insecta: Diptera). Annalen des naturhistorischen Museums in Wien (B), 87 [1983], 197 - 253.", "Malozemov, A. Yu. (1992) On the fauna and ecology of true flies (Diptera, Muscidae) of the eastern macroslope of the Pripolar Ural Mountains. In: Nikolaeva, N. V. (Ed.), Insects in natural and anthropogenic biogeocenozes of the Urals. Nauka, Yekaterinburg, pp. 91 - 93. [In Russian.]", "Robineau-Desvoidy, A. J. B. (1830). Essai sur les myodaires. Memoires presentes par divers Savans a l'Academie Royale des Sciences de l'Institut de France, Sciences Mathematiques et Physiques, (2) 2, 813 pp. [Publication date 6 June; see also under Wiedemann, 1830.]", "Hennig, W. (1961 a) Muscidae. [Part, Lieferung 215.] In: Lindner, E. (Ed.), Die Fliegen der palaearktischen Region, 63 b, 481 - 528. Schweizerbart, Stuttgart.", "Sorokina, V. S. (2006 a) Distribution and ecology of house-flies (Diptera, Muscidae) in West Siberia. Euroasian Entomological Journal, 5, 221 - 233. [In Russian, with English abstract.]", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215.", "Zetterstedt, J. W. (1845) Diptera Scandinaviae disposita et descripta. [Part.] Tomus quartus. Ex officina lundbergiana, Lundae [= Lund], pp. 1281 - 1738.", "Collin, J. E. (1963) The British species of Lispocephala (Diptera, Anthomyiidae). Entomologist, 96, 277 - 283."]}